Contemporary Rhetorical Citizenship - Kock, Christian; Villadsen, Lisa (Rhetoric in Society, 2015)
This book presents studies from different academic fields of theoretical issues raised by public discourse, focusing on understanding and evaluating how its many manifestations both reflect, shape, and challenge the society it is a part of. The book also presents analyses of examples from around the world of civic communication, ranging from public hearings about same-sex marriage over polemical letters to the editor to public displays of knitting as a protest form.